Disconnection from nature: Expanding our understanding of human-nature relations - Beery Thomas; Stahl Olafsson Anton; Gentin Sandra; Maurer Megan; Stålhammar Sanna; Albert Christian; Bieling Claudia; Buijs Arjen; Fagerholm Nora; Garcia-Martin Maria; Plieninger Tobias; M. Raymond Christopher (Wiley, 2025)
1. The human relationship with nature is a topic that has been explored throughout human history. More recently, the idea of connection to nature has merged as an important transdisciplinary field of study. Despite increased scholarly attention to connection to nature, the notion of disconnection from nature remains undertheorized and understudied.
2. In this perspective article, we argue for a more comprehensive understanding of disconnection from nature to strengthen theories of human-nature relationships that goes beyond individual relationships and considers social and collective factors of disconnection, including institutional, socio-cultural and power dimensions.
3. Drawing on case insights, we present the ‘wheel of disconnection’ to illustrate how disconnections from nature manifest across individual or societal meaning-making processes, thereby problematizing existing research that seeks to create dualisms between human positive and negative impacts on the environment in isolation from cultural or political contexts.
4. We do not seek to discount research or important practical efforts to foster an individual's connection to nature by elevating disconnection. Instead, we hope that creating greater awareness and understanding of disconnection will be able to guide opportunities going forward for strengthening a connection to nature along a continuum from the individual to the social.